A correlation study applied to biomarkers of internal and effective dose for acrylonitrile and 4-aminobiphenyl in smokers. (June 2014) - Scherer, Gerhard; Newland, Kirk; Papadopoulou, Ermioni; Minet, Emmanuel
Abstract The urinary metabolites 2-cyanoethylmercapturic acid and 4-aminobiphenyl have been correlated with tobacco smoke exposure. Similarly, 2-cyanoethylvaline and 4-aminobiphenyl haemoglobin adducts have been used as biomarkers of effective dose for the exposure to acrylonitrile and 4-aminobiphenyl, respectively. Each pair of biomarkers is derived from the same parent chemical; however, the correlation between the urinary and the haemoglobin biomarkers has not been investigated. Using clinical study samples, we report a weak correlation between urinary and haemoglobin biomarkers due to different accumulation and elimination rates. Time course analysis showed that a reduction in exposure was paralleled by a delayed reduction in haemoglobin adducts.